Depression as a consequence of female abuse between 15-30 years in Mariscal Sucre Parish 2019 (Horizontes de Enfermería, 2020)
The integrity of women has always been classified as the weaker sex and therefore the constancy of violence against them has been considered as a public health problem that affects the social, psychological, and physical situation, hindering their true performance in the characteristic society of depression. That is why the objective of this article was to relate the influence of depression in the daily life of women from post-traumatic stress as a result of violence in its different forms. In this context, social distension due to the lack of emotional support allowed us to know qualitatively the approach of the descriptive research. On the other hand, the quantification of the surveys was carried out on a sample of 101 women from the Mariscal Sucre Parish, based on the Yesavage Test and adjacent questions. It was observed that 40% of the respondents were positive to the test. Likewise, the continuation of the questions concluded that the nature of the woman tends to get depressed easily but when there is sentimental commitment such as free union couples and the violence involved, emotional stability is broken to the point of being frightened when sharing such experiences with others you trust.
Keywords: post-traumatic stress; depression; Yesavage Test